Selection criteria and index analysis for the S2 maize lines of double-crosses - ANNUR KHAINUN AKFINDARWAN; MUH FARID; SYATRIANTI ANDI SYAIFUL; MUHAMMAD FUAD ANSHORI; AMIN NUR (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Akfindarwan AK, Farid M, Syaiful SA, Anshori MF, Nur A. 2023. Selection criteria and index analysis for the S2 maize lines of double-crosses. Biodiversitas 24: 192-199. This study aimed to determine the selection criteria and the selection index for the S2 maize lineage from double cross crosses and to select the potential lines that could be continued in the S3 generation. The research was carried out in the field from July to November 2020 at the Experimental Farm of the Agriculture Faculty, Hasanuddin University, Tamalanrea District, Makassar City, South Sulawesi. The maize lines used were derived from 4 double cross populations of S1 generation, namely: DC1 (P36/B9//NK7328/JH2) with 19 genotypes, DC2 (B9)/HJ28/NK728), DC3 (B18/B2/B2/N29), and DC4 (JH45/B19/N29/B2). The results of this study revealed that the selection criteria suitable for this population were the weight of seeds per cob, peel cob weight, and weight of 100 seeds. Furthermore, the selection index analysis showed that there were 61 promising lines for F2 double cross maize that had a positive index value, while based on the Z value, there were 44 lines that had a better index value than the best parents. Therefore, it is recommended that the 61 S2 Maize lines from double crosses be further tested on to the S3 generation.